MARKETING COMMUNICATION STRATEGY FOR OIL PALM SEEDLINGS TO IMPROVE BRAND AWARENESS AT THE OIL PALM RESEARCH CENTER (PPKS) - Azzahra, Zakiya; Sikumbang, Ahmad Tamrin (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the marketing communication strategy of oil palm seedlings implemented by the Palm Oil Research Center (PPKS) in increasing brand awareness amidst agribusiness competition and the rampant circulation of illegal seedlings. This research is important because studies on marketing communications in the oil palm seed sector are still limited, while most previous studies have focused more on sales, general promotions, or marketing of consumer products, rather than on building brand awareness in the context of trust-based agribusiness. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research informants numbered six people consisting of PPKS management and consumers/users of oil palm seedlings. The results show that PPKS implements an integrated marketing communication strategy through online and offline channels, including the use of social media, the MySawit application, direct services, interpersonal communication, and education to farmers about the advantages of superior seedlings and the importance of purchasing through official channels. These findings indicate that PPKS brand awareness is not only shaped by the intensity of promotions, but also by the institution's credibility, the quality of educational messages, and long-term relationships with consumers. The contribution of this research lies in the affirmation that in the agribusiness sector, an effective marketing communication strategy is not only informative, but must be able to integrate education, trust, and institutional legitimacy to strengthen the brand's position in the market.